[A.V.I.D. class at Paso Robles High School] - Maria Campoverde::::::photographer::: (2005)
Description supplied by photographer: "En la escuela secundaria de Paso Robles durante la clase de A.V.I.D. En esta clase nos preparamos para el colegio. Esta es la mesa donde yo me siento con todas mis amigas a platicar." - "At Paso Robles High School during A.V.I.D. class. A.V.I.D. stands for 'Advancement Via Individual Determination.' It is a class that prepares us for college. I sit at this table and talk with my friends."